Küçük ve orta boy işletmelerde bilgi yönetimi - Koçak, Jülide (Gebze Yüksek Teknoloji Enstitüsü, Lisansüstü Eğitim Enstitüsü, 2004)
Küçük ve Orta Boy İşletmeler ( KOBİ' 1er ) bütün ülkelerin ekonomik yapılarında önemli bir yere sahiptirler. Artan rekabet karşısında KOBİ' lerin ayakta kalabilmeleri, onların Bilgi Yönetimi kabiliyetine bağlıdır. Bilgi yönetimi bilgiyi; elde etme, depolama, paylaşma ve bilgi seviyesini yükseltme sürecidir. Bireye veya organizasyona her türlü tecrübeyi kazandıracak, onlar arasında ilişki oluşturacak ve iş süreçlerine değer katacak her türlü faaliyet bilgidir. Ve bu bilgi organizasyonlar için başarının temelidir. Bu çalışma, bilgi ve iletişim teknolojilerinin ekonomi ve iş alanında kullanılması ile doğan ve bir bilgi çağı kavramı olan Bilgi Yönetimi' nin tanımım, sürecini ve uygulama basamaklarını irdelemektedir.

Small and Medium Sized Enterprises ( SMEs ) are having an important role in all countries economic structure. The ability of SMEs to survive in a harsh competitive environment is closely tied to their knowledge management. Knowledge management is a process of capturing, storing, sharing and leveraging knowledge. Every activity, which will give all kind of experiments to individual or organization, which will make a relationship between an organization and an individual, which will add value to business processes, is knowledge. And this knowledge is a base of success for organizations. The definition, process and application phases of knowledge management which is an information age concept that has occurred as the result of using information and communication technologies in the world of economy and business are given in this thesis.
Knowledge management in small and medium size enterprises
Keywords: İşletme; Business Administration